KNOWLEDGE, ATTITUDES, AND PRACTICES OF THE DEPOK COMMUNITY TOWARDS STROKE - Nathania, Valentine; Hidayat, Rakhmad (Acta Neurologica Indonesia, 2025)
Stroke is the number one cause of disability in the world and the number two cause of death in the world. Stroke is also the ninth cause of death in hospitals in Depok. Prehospital delays contribute greatly to poor stroke management. Therefore, the knowledge, attitudes and behavior of the Depok community towards stroke need to be assessed to find out the causes of pre-hospital delays. This research uses a descriptive design with a cross-sectional approach. The sampling technique used consecutive sampling techniques. Data was obtained using a questionnaire consisting of 12 knowledge component questions, 4 attitude component questions, and 3 behavior component questions. Of the 400 respondents representing the people of Depok, 82.5% have poor knowledge about stroke. A total of 60.75% of the people of Depok have a poor attitude toward stroke, and 56.25% of the people of Depok exhibit poor behavior towards stroke. The result shows that the majority of the people of Depok have inadequate knowledge, attitudes, and behaviors regarding stroke.